Lead-free low-dimensional tetraalkylammonium manganese- and copper-based hybrid organic–inorganic perovskites for visual fluorometric Pb2+ ion detection - Kour, Prachi; Sahu, Pragati; Dambhare, Neha V.; Rath, Arup Kumar; Mukherjee, Shatabdi Porel (ACS Applied Optical Materials, 2024)
For the first time, we have synthesized lead (Pb)-free manganese (Mn)- and copper (Cu)-based hybrid organic–inorganic perovskite (HOIP) compounds, compound 1, (TEA)2MnBr4, compound 2, (TBA)2MnBr4, compound 3, (TEA)2CuBr4, and compound 4, (TBA)CuBr2 (where TEA is tetraethylammonium and TBA is tetrabutylammonium), under ambient conditions via mechanochemical synthesis methodology using a Kakuhunter-made planetary mixer. The compounds are characterized as 2D except for (TBA)CuBr2, which has crystallized in the 0D lattice. The synthesized compounds are phase pure and show a stable solid-state emission at room temperature. The Mn-based perovskite compound 1 showed excellent environmental photostability for over a month and reasonable stability under a relative humidity of 70–80%. The nanoparticle (NP) dispersions of compounds 1 and 2 were used further for fluorescence titration studies using various heavy metal cations, including transition metals and lanthanides (e.g., Y3+, Nb3+, Co2+, Ni2+, Ag+, Zn2+, Cd2+, Pb2+, Gd3+, and Dy3+), where they showed good fluorescence switching by the Pb2+ ion. Compound 1 demonstrated excellent fluorescence switching performance with Pb2+ titration with a Pb2+ detection limit of 2.43 × 10–8 M and hence can be used to fabricate a Pb2+ calorimetric sensor. A preliminary visual thin film-based sensor using NPs of compound 1 was fabricated to test the change in emission from blue to green in correlation with the results obtained in the NP solution during Pb2+ ion sensing. A fascinating in situ ion-exchange-based mechanism for the sensitivity of NPs of compound 1 is confirmed. This study reveals the ability of Pb-free Mn-based HOIPs to detect an oxidizing metal cation, Pb2+, efficiently and quantitatively.

Rapid and efficient microwave-assisted synthesis of Mn-doped cesium bromide to phase engineered cesium manganese bromide nanocrystals with color-tunable RGB emission - Sahu, Pragati; Mukherjee, Shatabdi Porel (Journal of Materials Chemistry C, 2025)
Lead-free perovskite nanocrystals (NCs) have attracted considerable attention due to their excellent optoelectronic properties. However, they generally exhibit broadband emission with poor color purity. Similarly, obtaining tunable red/green/blue (RGB) emissions from lead-free perovskite NCs is highly desirable for several display applications. However, directly synthesizing lead-free perovskite NCs with tunable RGB emission and high color purity remains challenging. Herein, we have developed a simple and rapid microwave-assisted (MW-AT) synthesis strategy for synthesizing Mn-doped CsBr [Mn2+:CsBr] to phase engineering of non-toxic and stable all-inorganic cesium manganese bromide perovskite NCs in a nonpolar solvent with tunable blue-green-red emission color with high color purity. The phase transition was triggered by changing the MnBr2 concentration during the microwave synthesis: from Mn2+:CsBr (blue emission) to zero dimensional (0D) Cs3MnBr5 NCs (green emission) to one dimensional (1D) CsMnBr3 NCs (red emission). In addition, in a controlled moisture environment, both the 0D Cs3MnBr5 and 1D CsMnBr3 NCs were transformed into 0D Cs2MnBr42H2O NCs (blue emission), which could be inversely transformed back to their respective original phase via thermal annealing. Thus, our work highlights for the first time a rapid and efficient MW-AT synthesis strategy to obtain phase-pure tunable optical properties with high color purity from Mn-doped CsBr to cesium manganese bromide perovskite NCs via phase engineering, which can be further utilized in designing anti-counterfeiting and encryption materials for coding with high security and information concealment. Our work also provides a new avenue for exploring efficient MW-AT synthesis of other earth-abundant eco-friendly highly luminescent Pb-free perovskite NCs for future endeavors.